Obesity Before Birth Maternal and prenatal influences on the offspring - Lustig, Robert H.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2011)
Obesity obeys the First Law of Thermodynamics. The routine assumption is that obesity is the result of a mismatch between calories in and calories out; in other words, the result of two divergent behaviors. However, there is mounting evidence that biochemical forces can drive obligate weight gain, and that the observed behaviors of increased energy intake and decreased energy expenditure are secondary to these processes. Furthermore, many of these biochemical forces are determined in utero; resulting in a developmental drive toward obesity and disease in later life. Four distinct prenatal forces have thus far been identified: 1) genetics; 2) epigenetics; 3) developmental programming; and 4) environmental obesogens. This volume explores the evidence for each of these in detail in human and animal models, and attempts to provide a cohesive analysis of the biochemical bases of obesity. This volume will appeal to geneticists, developmental biologists, endocrinologists, epidemiologists, toxicologists, obstetrician/gynecologists, nutritionists, veterinary scientists, animal husbandry researchers, domestic species researchers, and obesity researchers and practitioners. "This very timely volume provides an in-depth scholarly overview of a critical challenge facing our society$1 (Bthe obesity epidemic. Dr. Robert H. Lustig has assembled expert authors to address the fundamental contribution of preprogrammed genetic disorders leading to obesity, as well as the role of very early environmental influences. The chapters range from classic genetic mechanistic understanding through intra-uterine epigenetic influences, factors determining developmental programming, and the new clinical science of perinatal obesogens. Obesity Before Birth: Maternal and prenatal influences on the offspring, brings easily accessible, cutting edge information to geneticists, pediatricians, endocrinologists, as well as those clinicians and scientists pursuing the complex yet elusive causes of childhood obesity and related disorders." - Shlomo Melmed, M.D. Series Editors
Preface -- Obesity: nature or nurture? -- The contribution of heredity to clinical obesity -- Monogenetic disorders within the energy balance pathway -- Ciliary syndromes and obesity -- Genome-wide association studies and human population obesity -- Known clinical epigenetic disorders with an obesity phenotype: Prader-Willi Syndrome and the GNAS locus -- Evidence for epigenetic changes as a cause of clinical obesity -- Epigenetic changes associated with intrauterine growth retardation and adipogenesis -- Exposure to diabetes in utero, offspring growth, and risk for obesity -- Maternal weight gain during pregnancy and obesity in the offspring -- Intrauterine growth restriction, small for gestational age, and experimental obesity -- Experimental models of maternal obesity and high-fat diet during pregnancy and programmed obesity in the offspring -- High carbohydrate intake only during the suckling period results in adult-onset obesity in mother as well as offspring -- Prenatal stress, glucocorticoids, and the metabolic syndrome -- Hypothalamic maldevelopment and developmental programming -- Adipocyte development and experimental obesity -- The obesogen hypothesis of obesity: overview and human evidence -- Perinatal exposure to endocrine disrupting chemicals with estrogenic activity and the development of obesity -- The role of environmental obesogens in the obesity epidemic.
Keywords: Medicine; Human genetics; Food science; Endocrinology; Medicine & Public Health; Endocrinology; Human Genetics; Food Science